Cucurbituril‐Encapsulating Metal–Organic Framework via Mechanochemistry: Adsorbents with Enhanced Performance. Issue 28 (9th June 2021) - Liang, Jun; Gvilava, Vasily; Jansen, Christian; Öztürk, Secil; Spieß, Alex; Lin, Jingxiang; Xing, Shanghua; Sun, Yangyang; Wang, Hao; Janiak, Christoph
Abstract: The first examples of monolithic crystalline host–guest hybrid materials are described. The reaction of 1, 3, 5‐benzenetricarboxylic acid (H3 BTC) and Fe(NO3 )3 ⋅9 H2 O in the presence of decamethylcucurbit[5]uril ammonium chloride (MC5⋅2 NH4 Cl⋅4 H2 O) directly affords MC5@MIL‐100(Fe) hybrid monoliths featuring hierarchical micro‐, meso‐ and macropores. Particularly, this "bottle‐around‐ship" synthesis and one‐pot shaping are facilitated by a newly discovered Fe‐MC5 flowing gel formed by mechanochemistry. The designed MC5@MIL‐100(Fe) hybrid material with MC5 as active domains shows enhanced CH4 and lead(II) uptake performance, and selective capture of lead(II) cations at low concentrations. This shows that host–guest hybrid materials can exhibit synergic properties that out‐perform materials based on individual components. Abstract : Mechanochemistry has been applied to achieve one‐pot fabrication of monolithic decamethylcucurbit[5]uril (MC5)‐encapsulating metal–organic frameworks. The designed MC5@MIL‐100(Fe) hybrid material with MC5 as active domains shows enhanced uptake, and selective capture of lead(II) cations at low concentrations. This work opens up the novel possibility of designing task‐specific porous host–guest hybrid materials on a macroscopic scale.